Correlation between coordination variability and sprint velocity in different skill level - Wang, L.; Qu, F.; Wang, W. (ISBS Proceedings Archive (Michigan), 2020)
The relationship between variability and motor performance may differ among different skill level subjects.The purpose of this study was to identify the relationship between coordination variability and sprint velocity in athletes group and non-athletes group. Continuous relative phase method was used to quantify the coordination variability across trials. The results suggest that the correlation between coordination variability and sprint velocity are different in athletes group and non-athletes group. For Hip-Knee coordination variability of braking phase, in athletes group, there was a significant negative correlation between variability and sprint velocity, the faster the velocity was, the less variability was. But in non-athletes group, the correlation was positive, the faster the velocity was, the greater variability was. This study has highlighted the effect of skill level on relationship between coordination variability and performance.